Tracheostomy co-colonization in autoimmune disease: beyond empiric treatment - Murad, Aimi Athirah Binti Azmi; Hui, Tan Sien (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
We report an unusual case of mixed Proteus mirabilis and Candida glabrata colonization of a tracheostomy tube in a patient with rheumatoid arthritis and Sjögren syndrome. Despite the striking appearance of blackish deposits on the tube surface, the patient was asymptomatic and endoscopic evaluation revealed no local pathology. The patient’s comorbidities likely contributed to altered airway microbial ecology, favoring biofilm persistence. Understanding biofilm behavior and differentiating colonization from infection prevented unnecessary antimicrobial therapy. This case highlights the importance of correlating microbiological findings with clinical and endoscopic assessments to guide management in chronic tracheostomy patients.